Challenges of scope definition for projects using conventional construction procurement method in Nigeria - Ameh, O. J.; Ogunyemi, A. B. (Penerbit UKM, 2015)
Embarking on capital project development without elaborate scope definition often results in disruption of production flow leading to rework, extension of project duration and cost overrun, and lowers the morale and productivity of the workforce. The major challenge facing most building and infrastructural projects in Nigeria is the absence of clearly defined project scope prior to construction project implementation. This study aimed at assessing the challenges and constraints to effective project definition in the Nigerian construction industry. Descriptive research design was adopted. Data were gathered through a survey questionnaire from Fifty-two construction professionals working in public organisations using purposive sampling technique. The data collected were analysed using both descriptive and inferential statistics. The result of the study revealed that project design parameters, project requirements, site information, project execution plan and business strategy are the five most important activity group required in project definition. The result also indicates that the major challenges militating against effective project definition are lack of knowledge of project definition process, initial problem represented by client’s information, insufficient time allocated to project definition, and information constraints among others. The practical implication of this study is that it highlights important activities that make a successful project scope definition and also major constraints faced by professionals during the scope development stage of projects.